Las Redes Sociales en el Norte de Chile A Spanish Translation of Social Media in Northern Chile (Why We Post, 2019)
This book, which is based on 15 months of ethnographic research in the city of Alto Hospicio in northern Chile, describes how its inhabitants use social networks and the effects on their daily lives. Nell Haynes argues that social networks are a place where residents of Alto Hospicio, or hospice, express their feelings of marginalization as a result of living in a city far from the national capital and with a notoriously low quality of life compared to other areas urban in Chile.